'So, do you miss clinical work?' Reflections on a journey through veterinary leadership. (2nd November 2019) - Elwood, Clive
Abstract : The author describes his path into and out of leading a large veterinary referral practice, and reflects on the challenges and rewards of leadership. Moving into a leadership role generally requires development of new skills and insight, and may mean old roles have to be passed on. The value of skills transferable from the clinic, such as listening, questioning, problem solving and trusting, are highlighted. The demands of task management, relationship management, external networking and change management are discussed. Reflecting from outside of the role, the importance of leadership development, self-care, daring, personal growth and change are acknowledged.